(untitled) (World Science, 2020)
The study of domestic philological education as a holistic and systemic phenomenon involves its study, both from the point of view of historical retrospective and in the context of modern innovative settings. Meanwhile, the scientific field related to the study of the interaction of traditions and innovations in the evolution of domestic philological education has not received due understanding by now. Within the framework of the indicated problem, questions arise, the solution of which in modern conditions has special acuteness and topicality. What are the trends and dynamics of changes in the interaction of traditional and new experience in the development of domestic philological education? What factors influence the nature of the interaction of traditions and innovations in the development of the theory and practice of domestic philological education? What does analysis and understanding of the interaction of traditions and innovations in the historical past of Russian philological education give to assess its current state and, no less important, to predict its future development? The list of these questions indicates the seriousness and scope of the study. The dynamism of global changes in the world, the change in the economic and socio-cultural patterns in the country contributed to the fact that higher education had to flexibly respond to the current situation in the training of personnel.